2012
DOI: 10.1097/dcc.0b013e3182445ff3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ventilator-Associated Pneumonia Through Aspiration of Subglottic Secretions

Abstract: Ventilator-associated pneumonia (VAP) is a subset of hospital-acquired pneumonias and is a serious, sometimes fatal, complication in patients who need mechanical ventilation. In addition, pay-for-performance initiative has placed increased emphasis on preventing nosocomial infections including VAP. Facilities may not be reimbursed for costs associated with prevalence infections. This article presents a review and meta-analysis of the prevention of VAP through the aspiration of subglottic secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…11,22 Among our sample, 6 patients with aspiration were intubated with a subglottic suction endotracheal tube, which is thought to reduce microaspiration. 23,24 However, 3 of the 4 patients with a traditional endotracheal tube had documented aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…11,22 Among our sample, 6 patients with aspiration were intubated with a subglottic suction endotracheal tube, which is thought to reduce microaspiration. 23,24 However, 3 of the 4 patients with a traditional endotracheal tube had documented aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…When only including studies that enrolled subjects expected to require (Table 2). [139][140][141][142] Regardless of the combination of the studies included in the analysis, the results suggest that SSD results in a reduction of VAP by ϳ50% and may be associated with reduced early onset of VAP, shorter duration of mechanical ventilation, and fewer days in the ICU, but not a reduced mortality.…”
Section: Subglottic Secretion Drainagementioning
confidence: 91%
“…However, SSD may also be associated with risks such as airway mucosal injury and bleeding, detection of which requires testing for occult blood. 10 Although the efficacy of SSD was in question in past decades, previous meta-analyses have consistently concluded that SSD reduces the rate of early-onset VAP, [11][12][13][14][15] and the use of SSD for VAP prophylaxis is highly recommended by guidelines and experts. 16,17 SSD may be performed as continuous SSD (CSSD) or intermittent SSD (ISSD).…”
Section: Zunjia Wen Is a Registered Nurse Haiying Zhang Is An Associmentioning
confidence: 99%